Dorsolateral prefrontal cortex excitability assessed using TMS‐EEG and its relationship with neuropsychiatric symptoms in Alzheimer's dementia: Neuropsychiatry and behavioral neurology/assessment/measurement of neuropsychiatric/behavioral and psychological symptoms. (7th December 2020) - Joseph, Shaylyn; Zomorrodi, Reza; Ghazala, Zaid; Knezevic, Dunja; Blumberger, Daniel M.; Daskalakis, Zafiris J.; Mulsant, Benoit H.; Pollock, Bruce G.; Rajji, Tarek K.; Kumar, Sanjeev
Abstract: Background: Neuropsychiatric symptoms (NPS) are common in patients with Alzheimer's Dementia (AD) and cause substantial distress to patients and caregivers. Mechanisms underlying NPS are not well known. Studies have found increased cortical excitability in patients with AD. Studies in other neuropsychiatric disorders have found increased cortical excitability in association with NPS. We hypothesized that cortical excitability will be negatively associated with cognition and positively associated with NPS in AD. Method: This cross‐sectional study included participants diagnosed with probable AD using the NIA‐AA core clinical criteria. Cognition was assessed using Montreal Cognitive Assessment (MoCA) and NPS were assessed using the Neuropsychiatric Inventory‐Questionnaire (NPI‐Q). NPIQ agitation‐hyperactivity domain scores were calculated by combining scores on agitation, aggression, anxiety, disinhibition and irritability domains. Motor threshold and Transcranial Magnetic Stimulation (TMS) intensity sufficient to induce 1 millivolt (mV) peak to peak motor evoked potential were calculated as per established methods. TMS at the 1mV intensity was applied to the dorsolateral prefrontal cortex (DLPFC) at a frequency of 0.1 Hz. Electroencephalography was collected during TMS. Cortical excitability was assessed using rectified area under the curve (AUC) for TMS‐evoked potential (TEP) during early (25‐80 ms) and late phases (80 – 200 ms). Individual TEP peak amplitudes were also calculated. Result: The study included 25 participants (female = 17, Mean (SD) age = 74.3(7.1) Years, Mean (SD) MoCA score = 17.5 (4.6)). There was a negative correlation between MoCA and the TEP early AUC at the DLPFC site of stimulation (Spearman's rs = ‐ 0.589, n = 24, p = 0.002). In contrast there was a positive correlation between NPI‐Q agitation ‐ hyperactivity domain scores and the TEP early AUC (Spearman's rs = 0.422, n = 24, p = 0.04). There was also a positive correlation between total NPIQ and early TEP (P30) amplitude. Conclusion: Cortical excitability in the DLPFC is inversely associated with cognition and positively associated with NPS in AD. Specifically, increased excitability found during the early TEP duration suggests potential role of aberrant glutamatergic transmission and overall gamma amino butyric acid and glutamate imbalance. These findings may have important implications for developing treatment interventions targeting cortical excitability in AD.